The role and opportunities of indigenous justice systems in promoting restorative justice - Husni Husni; Nurarafah Nurarafah; Joelman Subaidi; Johari Johari; Zulfan Zulfan (Indonesian Institute For Counseling, Education and Therapy, 2026)
The Indonesian criminal justice system struggles to achieve substantive justice due to the dominance of a retributive approach, resulting in prison overcrowding and high recidivism rates. Restorative justice offers an alternative emphasizing reconciliation and social balance, consistent with long-standing indigenous justice practices in the archipelago. This study analyzes the juridical construction of customary justice recognition within the national legal system, explores the opportunities and challenges of integrating it as an instrument of restorative justice, and formulates an ideal synergy model between customary and formal justice systems. This systematic review examines the role, opportunities, and challenges of indigenous justice systems in promoting restorative justice in Indonesia. Operating under a rigorous systematic protocol to eliminate convenience sampling bias, electronic searches were conducted across the Scopus, Web of Science, and Garuda databases using the query (indigenous justice or adat) and (restorative justice) Indonesia. Strict, explicit selection criteria requiring peer-reviewed journal articles published between 2021 and 2026 that directly analyze Indonesian customary law and localized restorative values narrowed a total of 142 initially identified articles down to exactly five core publications. Synthesizing these five selected studies reveals that formal recognition remains a primary opportunity, while human rights standardization and statutory synchronization present significant hurdles. Furthermore, conflict resolution effectiveness is highlighted through comparative illustrative examples extracted directly from the reviewed literature specifically focusing on the customary practices of the Baduy community and dispute resolution in Peniti Village rather than through empirical field data collected by the author. Ultimately, rather than overreaching to formulate an absolute ideal model, this targeted review proportionately proposes a conceptual framework and identifies key design principles to guide policymakers in harmonizing customary mechanisms with Indonesia's national criminal justice reform.